Physico-Chemical Parameterization and Comparison of Some Milks - Gautam, Madhab; Pantha, Sabina (Tribhuvan Journal, 2023)
Milk is a source of Lactose, Proteins, Fats, Vitamins, minerals, etc. This work was carried out to estimate and compare the physicochemical parameters of fresh milk and boiled milk of Human (woman), Cow, Buffalo and Goat of Palpa after one month of their pregnancy time in December, 2018and to compare these parameters with their standard values. These were analyzed using standard literature methods. I t has been determined that Fresh Human milk has 8.16 pH, 7.7 % Lactose, 3.30 %, Fat, 85 % Water, and 0.036mg Chloride, Fresh Cow milk has 6.68 pH, 3.7 % Lactose, 3.71 % Fat, 90 % Water, and 0.035mg Chloride, Fresh Buffalo milk has 6.07 pH, 3.8 % Lactose, 5.84 % Fat, 90 % Water, and 0.037 mg Chloride and Fresh Goat Milk has 6.81 pH, 3.1 % Lactose, 4.93 % Fat, 83.25 % Water, and 0.036 mg Chloride but 7.50 pH, 7.6 % Lactose, 3.11 %Fat, 71 % Water and 0.03249 mg Chloride in Human milk, 6.24 pH, 3.3 % Lactose, 3.21 % Fat, 79.5 % Water, and 0.03427 mg Chloride in Cow milk, 5.54 pH, 3.1 % Lactose, 5.74 % Fat, 88.5 % Water, and 0.01831 mg Chloride in Buffalo milk and 6.36 pH, 2.9 % Lactose, 4.37 % Fat, 79.5 % Water, and 0.04136 mg Chloride in Goat milk after boiling at 50°C respectively. All determined parameters of collected milk samples meet the standard requirements and boiled milk is found to be better than fresh milk.